Resource Use Impact of Management Strategies for Local Haemostasis and Sealing: the Surgeons’ Perspective - Viborg Mortensen, F.; Birth, M.; Günther, K.; Habicht, A.; Korsholm, L.; Bilde, L. (Gesundheitsökonomie & Qualitätsmanagement, 2012)
Aim: The aim of this study was to evaluate treatments for haemostasis and the potential hospital resource use implications of these treatments by way of expert assessment.Methods: This analysis was based on data from a non-interventional surveillance study, which enrolled 3098 patients at 227 centres in 12 European countries. All patients received a haemostatic sealing patch (TachoSil®, Nycomed GmbH, Zurich, Switzerland), with the decision to use TachoSil made by the surgeon. Data on duration of surgery, hospital length of stay (LOS) and use of blood products were collected. Surgeons were asked to compare TachoSil with products or procedures they would otherwise have used.Results: Mean duration of surgery was 192.1 minutes and mean hospital LOS was 17.5 days. According to surgeons, operating time would have been significantly reduced with TachoSil versus the potential alternative in 55.5 % of patients (p < 0.001). Surgeons predicted that the use of TachoSil would reduce duration of surgery by 12.2 minutes. Choice of alternative treatment, type of surgery and country had a significant effect on surgeons’ assessment. TachoSil was thought to offer greater benefits in anti-coagulated patients with a normal pre-operative coagulation test and in emergency surgery.Conclusion: The use of topical haemostatic agents such as TachoSil may offer benefits with regard to hospital resource use.
Keywords: surgery; haemostasis; haemostatic agents; tissue sealing; TachoSil